Cost per median overall survival month associated with abiraterone acetate and enzalutamide for treatment of patients with metastatic castration-resistant prostate cancer. (2nd August 2016) - Pilon, Dominic; Queener, Marykay; Lefebvre, Patrick; Ellis, Lorie A.
Abstract: Objective : To calculate costs per median overall survival (OS) month in chemotherapy-naïve patients with metastatic castration-resistant prostate cancer (mCRPC) treated with abiraterone acetate plus prednisone (AA + P) or enzalutamide.Methods : Median treatment duration and median OS data from published Phase 3 clinical trials and prescribing information were used to calculate costs per median OS month based on wholesale acquisition costs (WACs) for patients with mCRPC treated with AA + P or enzalutamide. Sensitivity analyses were performed to understand how variations in treatment duration and treatment-related monitoring recommendations influenced cost per median OS month. Cost-effectiveness estimates of other Phase 3 trial outcomes were also explored: cost per month of chemotherapy avoided and per median radiographic progression-free survival (rPFS) month.Results : The results demonstrated that AA + P has a lower cost per median OS month than enzalutamide (3231 vs 4512; 28% reduction), based on the following assumptions: median treatment duration of 14 months for AA + P and 18 months for enzalutamide, median OS of 34.7 months for AA + P and 35.3 months for enzalutamide, and WAC per 30-day supply of 8007.17 for AA + P vs 8847.98 for enzalutamide. Sensitivity analyses showed that accounting for recommended treatment-related monitoring costs or assuming identical treatment durations for AA + P and enzalutamide (18 months) resulted in costs per median OS month 8–27% lower for AA + P than for enzalutamide. Costs per month of chemotherapy avoided were 4448 for AA + P and 5688 for enzalutamide, while costs per month to achieve median rPFS were 6794 for AA + P and 7963 for enzalutamide.Conclusions : This cost-effectiveness analysis demonstrated that costs per median OS month, along with costs of other Phase 3 trial outcomes, were lower for AA + P than for enzalutamide. The findings were robust to sensitivity analyses. These results have important implications for population health decision-makers evaluating the relative value of therapies for mCRPC patients.